Lobbying on Entry - Enrico Perotti; Paolo Volpin (Tinbergen Institute, 2004)
We develop a model of endogenous lobby formation in which wealth inequalityand political accountability undermine entry and financial development. In-cumbents seek a low level of effective investor protection to prevent potentialentrants from raising capital. They succeed because they can promise largerpolitical contributions than the entrants due to the higher rents earned withless competition. Entry and investor protection improve when wealth distribu-tion becomes less unequal, and the political system becomes more accountable.Consistent with these predictions, in a cross-section of 38 countries we find that greater accountability is associated with higher entry in sectors that are more dependent on external capital and have greater growth opportunities. Also,higher accountability and lower income inequality are associated with more ef-fective legal enforcement, even after controlling for legal origin and per-capita income.
Keywords: G21; G28; G32; 330; Politics; Entry; Financial Development; Entrepreneurship; Investor protection; Income Inequality; Growth; Interessenpolitik; Markteintritt; Anlegerschutz; Vergleich; Welt